The persistence of necropolitics: violence against indigenous environmental defenders in Peru - De La Cruz Huamán, Rosario Betzabeth (2023)
This article analyzes the violence exerted against men and women indigenous environmental defenders in Peru. It should be noted that the defenders have been carrying out relevant work in the protection of their territories and forests, which have a favorable impact on their communities and on global society, especially in the current context of the climate crisis. However, although there are a number of international and national regulatory advances to protect the rights of indigenous peoples, there is a gap in their application which, on the one hand, suggests the persistence of violence and, on the other hand, a necropolitical set in motion: they are seen and treated as enemies “opponents of progress” and, consequently, they are victims of acts of violence that, in some cases, have even led to death. Faced with this, in recent years, the State has adopted a series of specific measures to protect and prevent this situation; however, there are significant difficulties in its implementation, which places them in a situation of vulnerability and, simultaneously, reinforces the naturalization of this necropolitical practice in the social imaginary.